Factors affecting the risk of gender-based violence among 2SLGBTQIA+ adolescents and youth: a scoping review of climate change-related vulnerabilities - Parzniewski, Szymon; Luo, Xing; Ru, Siyu; Ozbilge, Nevcihan; Breen, Kyle; Wu, Haorui (Frontiers in Sociology, 2025)
Gender-based violence (GBV) is a pervasive and growing issue that affects diverse populations worldwide. This study aimed to synthesize the factors affecting the risk of GBV among 2SLGBTQIA+ adolescents and youth. A scoping review was conducted using international databases (Web of Science, Scopus, Proquest, PubMed, Embase, EBSCOhost) since 2009. The studies were independently appraised by two reviewers guided by the PRISMA approach. Ninety-nine articles focusing on the 2SLGBTQIA+ community, GBV, and adolescents or youth were included for the review. The factors affecting the risk of GBV among 2SLGBTQIA+ adolescents and youth were categorized into (1) Wellbeing and mental health; (2) Disparities compared to cisgender youth; (3) Perpetration and victimization; (4) Different types of violence; and (5) Differences among 2SLGBTQIA+ subgroups. The studies further showed relevance to climate-related stressors such as displacement and resource scarcity, and how those can further amplify the vulnerabilities of 2SLGBTQIA+ youth to GBV. The findings revealed the necessity for multi-level strategies that account for the compounded risks faced by 2SLGBTQIA+ adolescents and youth, including those introduced by environmental crises. These five factors related to GBV among 2SLGBTQIA+ adolescents and youth should be considered by social work professionals when working with at-risk populations. Due to limited robust evidence (from countries outside the US) and the diverse contexts of the selected studies, future research is needed to minimize GBV among 2SLGBTQIA+ adolescents and youth, especially as climate change introduces new layers of vulnerability.Systematic review registration10.37766/inplasy2024.4.0008